Taekwondo sporunda farklı yük ve hareket paternlerindeki kas aktivasyonu sonrası potansiyelin vuruş performansına etkisinin incelenmesi - Cumbur, Cansel (My University, 2023)
Amaç: Bu çalışmanın amacı, farklı yük ve hareketlerle uygulanan akstivasyon sonrası potansiyel protokollerinin taekwondodaki vuruş hızı ve hareket süresine olan etkilerinin incelenmesidir. Gereç ve Yöntem: Çalışma; elit düzeyde gönüllü 10 erkek Taekwondo sporcusu (yaş 20,5±1,1 yıl; boy 1,76±3,8 cm; kilo 68,2±7,2 kg) ile gerçekleştirilmiştir. Yüklenme sonrası aktivasyon potensiyelini ölçmek üzere, geleneksel germe, direnç lastiği, squat (1TM %80), pliometrik ve squat (1TM %80) + direnç lastiği egzersizlerinden oluşan beş farklı protokol uygulanmıştır. Her protokol sonrası, gönüllülerin vuruş performansları cansız mankene yapılan vuruşlar ile ölçülmüştür. Vuruşun yapıldığı hedef noktası ivmelenmesi, hedefe yerleştirilen ivmeölçer (Xsens) sensörler ile gerçekleştirilmiştir. Hareket süratinin tespiti ise, özel tasarlanmış görsel reaksiyon sistemi ile ölçülmüştür. Bulgular: Geleneksel germe protokolü sonrası hedef noktası ivmelenme değerlerine göre; squat (1TM %80) egzersizi ile yapılan egzersizler sonrası ivmelenme değeri % 9.6, direnç lastiği ile yapılan egzersizler sonrası ivmelenme değeri %6.6 daha yüksek olduğu tespit edilmiştir. Squat + direnç lastiği ile yapılan egzersiz sonrası geleneksel germe protokolüne göre hareket süresinin (%7.3) daha da uzadığı görülmüştür. Sonuç: Taekwondo sporunda direnç lastiği ve squatla yapılan egzersizler sonrası vuruş performansını akut olarak iyileştiği ancak, direnç lastiği ve squat uygulamasının birlikte yapıldığı uygulamalarının hareket süratini uzattığı tespit edilmiştir. Müsabaka öncesi direnç bantları veya squat ile yapılan uygulamaların vuruş ivmelenmesini arttırmak için kullanılabileceği düşünülmektedir.

Objective: The aim of this study was to investigate and compare the Post Activation Potentiation (PAP) effects of different exercise patterns and, loads on acceleration of strike point and movement duration, a direct indicator of performance, in taekwondo athletes. Materials and Methods: Ten elite male taekwondo athletes aged 18-25 (20,5±1,1) years were participated in the study. The experimental design consisted of a warm-up, a post activation potentiation training protocol, and measurements to assess striking performance. The PAP training protocol includes five different exercises: traditional stretching, elastic band exercises, squats (80% of 1RM), plyometric exercises, and a combination of squats and elastic band exercises. Following each PAP exercise, the performance of the taekwondo athletes was assessed during the strikes to the mannequin. The acceleration of the target was measured using an accelerometer (Xsens) attached to the mannequin and the speed of movement was measured using a specially designed visual reaction system. Results: It was found that, compared to the traditional warm-up protocol, the PAP technique with squat (80% of 1RM) resulted in a 9.6% higher acceleration and, the PAP technique with elastic band 6.6% higher acceleration. In addition, the movement speed after the PAP technique using a combination of squats and elastic band exercises decreased by 7.3% compared to the traditional warm up. Conclusion: In conclusion, the PAP application using either the elastic band or squat exercises resulted in acute improvements on striking performance in taekwondo athletes. However, the PAP application using the combination of these exercises had a negative effect on movement speed. It is believed that PAP protocols performed using resistance bands or squat exercises can be utilized to enhance striking acceleration prior to competition.
Investigation of the effect of post activation potentiation different load and movement patterns on striking performance in taekwondo athletes
Keywords: Dövüş sanatları; kick acceleration; Martial arts; Öğrenim ve öğretim; PAP; post activation potentiation; post activation potentiation (PAP); strike force; Study and teaching; Taekwondo; Tekvando; vuruş ivmesi; vuruş kuvveti